Evolution of carbon capture and storage research: Trends of international collaborations and knowledge maps. (June 2015) - Karimi, Faezeh; Khalilpour, Rajab
Graphical abstract: Highlights: Study the evolution of international collaborations and major research topics on CCS. The CCS publications have exponentially increased within 1997–2009. A notable development in interconnectivity of CCS collaboration network & knowledge web. Results show a close relation of CCS research with international negotiation on CCM. Abstract: This study investigates the evolutionary trends of the international collaborations among the research community of carbon capture and storage (CCS) by looking at the collaboration network of countries publishing on CCS. The study also examines the evolution of major research topics in this field by exploring the co-occurrence network of keywords associated with CCS publications. The analysis is carried out based on the CCS related publications extracted fromScopus.com from 1980 to 2013. From the number of annual CCS publications, it seems that CCS research has closely followed the trend of international negotiations on climate change mitigation. The study elaborates how both international collaboration network and knowledge structure of the field have notably developed and interlinked over the years especially after 2005 during which almost 94% of the publications appeared.